Comparative Discourse Analysis and the Translation of Psalm 22 in Chichewa, a Bantu Language of South-Central Africa - Wendland, Ernst R. (Edwin Mellen Press, 1993)
This study illustrates a comprehensive method of analyzing the discourse structure and style of a Hebrew lyric text with special reference to its interacting thematic organization and rhetorical dynamics. An illustrated survey of 10 of the principal stylistic features leads to a discussion of similar rhetorical techniques manifested by modern lyric (written) poetry in Chichewa. The study also seeks to makes a contribution to the theory and practice of meaning-oriented Bible translation.